Camera trap detection of mycophagy among co‐occurring vertebrates. (13th December 2020) - Elliott, Todd F.; Vernes, Karl
Abstract: Thirty camera traps were deployed for a total of 4179 trap‐nights between January and June 2020 as part of a project assessing post‐fire recovery of pademelons ( Thylogale spp.) in northern New South Wales. By chance, one camera documented a site that was highly productive for the ectomycorrhizal fungal genus Amanita . This camera provided a rare opportunity to document a diversity of co‐habitating vertebrates that utilise these ectomycorrhizal fungi for food and in turn perform an important ecosystem function through the dispersal of their spores. Our camera recorded eleven vertebrate species; of these, we captured photographic evidence of Australian brush‐turkeys ( Alectura lathami ), a parma wallaby ( Notamacropus parma ), long‐nosed bandicoots ( Perameles nasuta ), red‐legged pademelons ( Thylogale stigmatica ) and red‐necked pademelons ( T. thetis ) feeding on fungal fruiting bodies. Abstract :